1986
DOI: 10.2214/ajr.146.2.211
|View full text |Cite
|
Sign up to set email alerts
|

"Horseshoe" lung: report of five new cases

Abstract: Case MaterialWe identified five patients at the Hospital for Sick Children in Toronto with the horseshoe lung anomaly and reviewed their chest radiographs, angiographic studies in four patients, and pathologic material in four patients, including a postmortem bronchogram in one patient.The diagnosis of horseshoe lung anomaly was made from pulmonary angiography in four patients and confirmed at autopsy in three of these, from pulmonary angiography alone in one patient, and from autopsy findings alone in one pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 4 publications
2
14
0
1
Order By: Relevance
“…The horseshoe or crossover lung anomaly may occur, as in patient 4, and is another common malformation associated with scimitar syndrome [6,8,9,21]. Airway anomalies, although common, do not seem to be major factors for symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…The horseshoe or crossover lung anomaly may occur, as in patient 4, and is another common malformation associated with scimitar syndrome [6,8,9,21]. Airway anomalies, although common, do not seem to be major factors for symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Horseshoe lung is an anomaly in which parts of the right and left lungs are fused together by a tongue of parenchyma posteroinferior to the pericardial reflection at the cardiac apex (Freedom et al 1986). It is usually associated with scimitar syndrome, which consists of partial anomalous pulmonary venous drainage of the right lung, right lung hypoplasia, dextroposition of the heart, and anomalous systemic arterial supply from the aorta to the right lung.…”
Section: Horseshoe Lungmentioning
confidence: 99%
“…Up to 2001, Männer et al (2001) described that almost 40 cases had been reported in the literatures since the first report by Spencer (1977). Regarding the fused part of these two lungs, two patterns have been reported: one in which the fusion was within the isthmus, and the other in which the fused tissue was separated by a fissure-like layer of visceral pleura (Freedom et al 1986). The right lung has often been reported as hypoplastic and lacking normal identifiable fissure and lobes, whereas the left lung has usually had a more normal appearance (Freedom et al 1986).…”
Section: Horseshoe Lungmentioning
confidence: 99%
See 2 more Smart Citations